2004
DOI: 10.1038/modpathol.3800198
|View full text |Cite
|
Sign up to set email alerts
|

BRAF mutations in anaplastic thyroid carcinoma: implications for tumor origin, diagnosis and treatment

Abstract: Anaplastic thyroid carcinoma is a highly aggressive neoplasm. Affected patients typically present with advanced disease where there is little hope for cure using conventional therapeutic modalities. Understanding the genetic alterations underlying the development of anaplastic thyroid carcinoma, such as mutational activation of BRAF, could help clarify its relationship with well-differentiated forms of thyroid carcinoma (ie follicular and papillary carcinoma) and could help select patients most likely to benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
91
0
7

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(102 citation statements)
references
References 21 publications
4
91
0
7
Order By: Relevance
“…22 Early work suggested that altered BRAF is an adverse prognostic variable due to its association with unfavorable clinicopathological characteristics such as older age, male gender, and distant metastasis, and the high prevalence of BRAF mutations in the clinically aggressive tall-cell variant of papillary carcinoma and poorly differentiated and undifferentiated carcinomas. 16,18,21,22,49,51,52 However, BRAF V600E is also found in papillary thyroid microcarcinoma, a tumor that is typically benign and often discovered as an incidental finding, as well as in pre-malignant colorectal and nevocellular lesions, suggesting that an activating mutation in BRAF occurs early in the initiation of papillary thyroid neoplasia and may additionally confer susceptibility for malignant progression. 12,17,18,[53][54][55][56] Compatible with this interpretation, one of the three tumors harboring BRAF V600E in this study was clinically indolent, whereas two behaved aggressively.…”
Section: Discussionmentioning
confidence: 99%
“…22 Early work suggested that altered BRAF is an adverse prognostic variable due to its association with unfavorable clinicopathological characteristics such as older age, male gender, and distant metastasis, and the high prevalence of BRAF mutations in the clinically aggressive tall-cell variant of papillary carcinoma and poorly differentiated and undifferentiated carcinomas. 16,18,21,22,49,51,52 However, BRAF V600E is also found in papillary thyroid microcarcinoma, a tumor that is typically benign and often discovered as an incidental finding, as well as in pre-malignant colorectal and nevocellular lesions, suggesting that an activating mutation in BRAF occurs early in the initiation of papillary thyroid neoplasia and may additionally confer susceptibility for malignant progression. 12,17,18,[53][54][55][56] Compatible with this interpretation, one of the three tumors harboring BRAF V600E in this study was clinically indolent, whereas two behaved aggressively.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the BRAF V600E mutation has been frequently found in microcarcinomas of the thyroid (30), which suggests a role in tumor initiation rather than tumor progression. On the other hand, BRAF mutations are also found in poorly differentiated and anaplastic thyroid carcinomas, suggesting that they may play a role in their highly aggressive behavior (7,11,39,40). In the study of Nikiforova et al (7), all BRAF-mutant poorly differentiated and anaplastic carcinomas contained areas of preexisting papillary carcinoma, and the BRAF V600E mutation was present in both the well-differentiated and dedifferentiated components, suggesting that it may have contributed to the transition from PTC to anaplastic carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…When multi-step carcinogenesis is taken into account, a considerable number of anaplastic carcinomas with BRAF mutations should be found. In previous reports, however, the frequency of the BRAF mutation was only about 10% on average and ranged from 0 to 63% (Fukushima et al, 2003;Namba et al, 2003;Nikiforova et al, 2003;Begum et al, 2004;Soares et al, 2004;Xing et al, 2004;Quiros et al, 2005). Among these studies, some reported that the BRAF mutation is found frequently only in anaplastic carcinomas with a papillary carcinoma component, although these studies have examined only four or five cases.…”
mentioning
confidence: 94%